CHALLENGES OF THE FINANCIAL MARKET OF UKRAINE IN TODAY’S CONDITIONS - Маршук, Ліна; Гатаулліна, Ельміра (Modern engineering and innovative technologies, 2023)
In a market economy, temporarily unused funds of various market subjects are accumulated, and then distributed and redistributed to various areas of the economy in the form of loans and investments to promote the economic development of various sectors of